Re-storying Grant Creek: relational restoration on a degraded Montana Stream - Seamus R. Land; Daniel T. Spencer (Ecosystems and People)
The ‘relational turn’, proposed for the sustainability sciences, provides an ontological and methodological means to move beyond positivist portrayals of ecological restoration in social-ecological systems towards what we call relational restoration. The proposed restoration of Grant Creek, a degraded stream near Missoula, Montana, is a socially rich and ecologically dynamic case study of restoration planning. This essay combines biophysical and sociological data to demonstrate that relational approaches and understandings of nature-human connectedness offer improved restoration opportunities, both in terms of ecological markers and for projects of conflict resolution and human justice. To gain a more holistic, dynamic understanding of the nature-human connectedness in the Grant Creek watershed, we combined a biophysical NRCS Riparian Assessment on 11 miles of stream with 20 in-depth interviews with landowners. We argue that local ecological knowledge, ethics, and stewardship practices need to be examined in conversation with traditional environmental science and management during restoration planning. The findings highlight the value of investigating restoration planning through a relational approach, offering a path through which the practice of ER, as conceived by the UN Decade on Ecosystem Restoration, might achieve several important outcomes: operationalizing social-ecological dynamics for local planning processes, identifying existing local relational dynamics, describing root causes of degradation, and creating space for more inclusive collaborative restoration processes. We conclude with caution, noting that despite these innovations, relational restoration needs additional justice considerations to properly consider North American Indigenous history and sovereignty.